Defects in Androgen Biosynthesis Causing 46,XY Disorders of Sexual Development - Auchus, Richard J.; Miller, Walter L. (Seminars in Reproductive Medicine, 2012)
At least one genetic defect in each reaction of the classical androgen biosynthesis pathway has been described. For some steps, such as the conversion of cholesterol to pregnenolone and the 17,20-lyase reaction, two or three genetic defects cause similar disorders with overlapping phenotypes and biochemical profiles. The elucidation of the molecular basis for these diseases has helped to define the pathways, essential genes, and enzymatic steps required to make androgens, and this knowledge is being exploited to develop better treatments of androgen-dependent diseases. Furthermore the description of nonclassical lipoid CAH and the protean manifestations of P450 oxidoreductase (POR) deficiencies has expanded the spectrum of human disease caused by disordered steroidogenesis. Finally, the recognition of the backdoor pathway to DHT has added a new dimension to our understanding of how steroid flux is maintained in normal and pathologic states.The traditional view of male external genital development has been that fetal testicular testosterone is converted to DHT by 5α-reductase Type 2 in genital skin, which then acts in a paracrine fashion to stimulate fusion of the labio-scrotal folds and phallic growth. This view is consistent with the incomplete external genital development in persons with severe deficiencies of 5α-reductase type 2. The new observations concerning AKR1C2/4 and the backdoor pathway indicate that DHT produced in the testis via the backdoor pathway also acts as a hormone to induce labio-scrotal fusion. Thus, both the classic and backdoor pathways are needed, and DHT acts in male genital development as both a paracrine factor and as a hormone. These surprising findings are revising our understanding of the mechanisms by which male sexual differentiation occurs, and illustrate the importance of detailed studies of rare patients with 46,XY DSD.
Keywords: androgen; testosterone; 46,XY DSD; congenital adrenal hyperplasia; testis; steroid; steroidogenesis; enzyme